'It's about the whole family': family contact for children in kinship care. Issue 2 (20th February 2014) - Kiraly, Meredith; Humphreys, Cathy
Abstract: Contact with family for children in care is identified as a right under the United Nations Convention on the Rights of the Child. However, such contact often presents challenges because of the protective concerns that have led to care arrangements being made. The Family Links: Kinship Care and Family Contact research study explored the nature and extent of family contact in kinship care, with a particular focus on the circumstances that create positive contact and foster family relationships. Findings included evidence of a large proportion of parental contact that was negatively affecting children's well‐being, and was sometimes unsafe. By contrast, the frequent contact that children were enjoying with their siblings and wider family was reported to be mostly positive and supportive. Kinship carers described a range of services needed to facilitate more positive parental contact and to enable children to keep contact with significant family members.